Supplemental Activator and Reducing Agent Atom Transfer Radical Polymerization: exploring new solvent systems and development of tailor-made block copolymers - Mendes, Joana Serra e Moura Pacheco (2018)
Doctoral Thesis in Chemical Engineering, submitted to the Faculty of Science and Technology of the University of Coimbra